2019
DOI: 10.3892/ol.2019.11044
|View full text |Cite
|
Sign up to set email alerts
|

Slow skeletal muscle troponin T, titin and myosin light chain 3 are candidate prognostic biomarkers for Ewing's sarcoma

Abstract: Ewing's sarcoma (ES) is a common malignant bone tumor in children and adolescents. Although great efforts have been made to understand the pathogenesis and development of ES, the underlying molecular mechanism remains unclear. The present study aimed to identify new key genes as potential biomarkers for the diagnosis, targeted therapy or prognosis of ES. mRNA expression profile chip data sets GSE17674, GSE17679 and GSE45544 were downloaded from the Gene Expression Omnibus database. Differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Further query at the Molecular Signature Database 10,11 showed that 53 (15.5%) of those 341 genes overlapped with a gene set overexpressed in mesenchymal stem cells with induced expression of the EWSR1::FLI1 fusion transcript 15 (Figure 4A). Of those, NKX2‐2 has been extensively studied in BST ES 16 and TNNT1 seems to be a promising biomarker of adverse behaviour 17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further query at the Molecular Signature Database 10,11 showed that 53 (15.5%) of those 341 genes overlapped with a gene set overexpressed in mesenchymal stem cells with induced expression of the EWSR1::FLI1 fusion transcript 15 (Figure 4A). Of those, NKX2‐2 has been extensively studied in BST ES 16 and TNNT1 seems to be a promising biomarker of adverse behaviour 17 …”
Section: Resultsmentioning
confidence: 99%
“…Of those, NKX2-2 has been extensively studied in BST ES 16 and TNNT1 seems to be a promising biomarker of adverse behaviour. 17 In ALES 461 genes where differentially expressed from BST ES, of which 395 (85.7%) overexpressed and 66 (14.3%) underexpressed. In relation to nonneoplastic thyroid tissue ALES had differential expression of 1346 genes, of which 682 (50.7%) were upregulated and 664 (49.3%) were underexpressed.…”
Section: R N a E X P R E S S I O N P R O F I L I N Gmentioning
confidence: 98%
“…On the other hand, high expression of TTN and MYL3 genes can be described as a biomarker of a worse prognosis in Ewing’s sarcoma [ 52 ]. TTN was also reported to be more expressed in gastric adenocarcinoma [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to GO and KEGG analysis, we discovered that these MRGs in uenced the prognosis of Ewing's sarcoma mainly through the following functions and pathways, including small molecule catabolic process, coenzyme binding, arginine and proline metabolism, tyrosine metabolism and fatty acid degradation. The role of the regulation of small-molecule metabolic processes, cofactor-binding, amino acid, proteasome and ribosome biosynthesis in eukaryotes in Ewing's sarcoma development and prognosis has been identi ed and validated by studies [16] . In the mitochondria of malignantly proliferating tumor cells, some necessary metabolic processes occur, such as the oxidative metabolism of glucose and glutamine to produce citrate and acetyl-CoA, which are involved in the synthesis of lipids.…”
Section: Discussionmentioning
confidence: 99%